Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1021/ed071p624
|View full text |Cite
|
Sign up to set email alerts
|

Verification of the Schulze-Hardy Rule: A Colloid Chemistry Experiment

Abstract: A simple and inexpensive experiment for verifying the Schulze-Hardy rule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 1 publication
(1 reference statement)
2
25
0
Order By: Relevance
“…3d). This fits with the observations by Liang and Morgan (1990), who concluded that Ca is more effective than Na as a coagulant of Fe 2 O 3 particles as can be qualitatively predicted by the SchulzeHardy rule (Nowicki and Nowicka, 1994). ADVA ® Cast 550 stabilized the Fe 2 O 3 colloids to higher concentrations of Ca(OH) 2 , keeping the Zeta potential of the colloids around neutral values.…”
Section: Effect Of Phsupporting
confidence: 89%
“…3d). This fits with the observations by Liang and Morgan (1990), who concluded that Ca is more effective than Na as a coagulant of Fe 2 O 3 particles as can be qualitatively predicted by the SchulzeHardy rule (Nowicki and Nowicka, 1994). ADVA ® Cast 550 stabilized the Fe 2 O 3 colloids to higher concentrations of Ca(OH) 2 , keeping the Zeta potential of the colloids around neutral values.…”
Section: Effect Of Phsupporting
confidence: 89%
“…[10] However, synthesis of atomically precise alloy QCs of various compositions is a challenge. [11] Murray et al synthesized Pd@Au 24 (SR) 18 which was further studied by Negishi et al [ 11b] Negishi et al isolated PdAu 24 (SR) 18 .…”
mentioning
confidence: 99%
“…Ag n Au 25Àn (SR) 18 , and (AuAg) 140 (SR) 60 (R = organic soluble alkyl/aryl groups) were obtained by simultaneously reducing metal salts in suitable conditions. [11c,d] There is also a family of well-characterized Ag/ Au/Cu cluster complexes [12] that are different from the metal core clusters discussed herein.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is because CCC is very sensitive to the valence of counterions. As indicated by the Schulze-Hardy rule, 27,28 for low surface potential colloid systems, the CCC is inversely proportional to the second power of the counterion valence; for high surface potential colloid systems, the CCC is inversely proportional to the sixth power of the counterion valence. Figure 5 shows the titration results with the two monovalent salts.…”
Section: Effects Of Titrant Type Titrant Concentration and Titratiomentioning
confidence: 99%